What did Isaiah Berlin Have to Say about Rousseau - and Why so Little? - Wendland, Michał (Sensus Historiae, 2022)
Isaiah Berlin was widely known as one of the most influential theorists of the Enlightenment and Counter-Enlightenment philosophy. In his may seminal essays, Berlin constructed a distinctive interpretation of these intellectual currents. As a recognized thinker, yet not free from some controversies, Berlin had not only criticized Enlightenment himself (thereby joining many contemporary detractors of the Enlightenment, e.g. Adorno, Gray, Becker, Koselleck), but also identified some figures of most importance for contesting “„the Age of Lights” and its heritage (e.g. Herder, Hamann, Fichte, de Maistre, Vico). HBerlin, however, head almost completely omitted one of the most significant philosophers of the 18th century, Jean-Jacques Rousseau. The vast majority of contemporary researchers perceive Rousseau and his philosophy as the keystone of Counter-Enlightenment, whereas in Berlin’s works Rousseau remains almost ignored. The aim of this article is to examine the reasons forof such a curious omissiontment, and to determine why Berlin’s works, once so influential, are nowadays so heavily criticized so heavily by many historians and philosophers (e.g. B. Yack, M. Lilla, G. Garrard, D. MacMahon).